The Influence Of Entrepreneurial Characteristics And The Utilization Of Digital Media On The Success Of Culinary Msmes In Medan Deli District (With The Object Of Msmes Using Digital Media) - Elisabeth Nainggolan; Sri Rezeki; Afrizal Afrizal; Padila Dwi Kusuma (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of Entrepreneurial Characteristics and Digital Media Utilization on the Success of Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector in Medan Deli District. Culinary MSMEs play a significant role in the local economy, particularly in creating jobs and increasing community income. However, many culinary MSMEs in Medan Deli District face challenges in developing their businesses, such as a lack of confidence in taking risks and limited use of digital media to expand their markets. In this study, entrepreneurial characteristics such as leadership, risk-taking courage, and the ability to innovate are identified as key factors in business success, while the use of digital media is expected to increase market reach and operational efficiency of culinary businesses. This study uses multiple linear regression methods to analyze the relationship between these two independent variables and the success of culinary MSMEs. The results of this study are expected to provide insights and recommendations for culinary MSMEs in Medan Deli District to optimize their entrepreneurial potential and utilize digital technology to achieve greater success in their businesses.